2016
DOI: 10.1039/c6np00039h
|View full text |Cite
|
Sign up to set email alerts
|

Nauclea latifolia: biological activity and alkaloid phytochemistry of a West African tree

Abstract: Covering up to 2016Nauclea latifolia (syn. Sarcocephalus latifolius, Rubiaceae), commonly called the African pincushion tree, is a plant widely used in folk medicine in different regions of Africa for treating a variety of illnesses, including malaria, epilepsy and pain. N. latifolia has not only drawn the interest of traditional healers but also of phytochemists, who have identified a range of bioactive indole alkaloids in its tissue. More recently, following up on the traditional use of extracts in pain mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 71 publications
(152 reference statements)
0
24
0
1
Order By: Relevance
“…Plants and microbes have provided humankind with some of the most clinically relevant drugs and secondary metabolites with beneficial effects on various ailments including pain relief. For example, some recent successful cases reported are indole alkaloids from Nauclea latifolia 40,41 and Corydalis yanhusuo 42 , and diterpene glucosides from Rhododendron micranthum 43 . Flavonoids are an important class of phytochemicals ubiquitously existing in the plant kingdom and have members that are considered promising candidates for natural analgesics 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Plants and microbes have provided humankind with some of the most clinically relevant drugs and secondary metabolites with beneficial effects on various ailments including pain relief. For example, some recent successful cases reported are indole alkaloids from Nauclea latifolia 40,41 and Corydalis yanhusuo 42 , and diterpene glucosides from Rhododendron micranthum 43 . Flavonoids are an important class of phytochemicals ubiquitously existing in the plant kingdom and have members that are considered promising candidates for natural analgesics 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory activity of this class of phytochemical has been well reported such as the erythrocyte membrane stabilising effect, cation-binding activity of tannins and wound healing properties of lycopene and β-carotene [36][37][38]. Boucherle et al [39] reported the presence of tannins in the leaf extract of N. latifolia buttressing findings 9 Oxidative Medicine and Cellular Longevity usually witnessed with synthetic inhibitors such as acarbose and voglibose [15,42]. This study revealed the promising inhibitory α-amylase and α-glucosidase potential of N. latifolia leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main directions of the development of chemistry is the search for substances with high biological effect, which can become the base for the creation of new biologically active substances that would be competitive as potential medicines in the market of imported and domestic products. Nitrogencontaining heterocyclic compounds are known as natural and synthetic molecules [1,2] that exhibit a wide range of biological effects [3][4][5]. Among various N-heterocycles, pyrrolo[1,2-a]quinoline derivatives attract considerable attention due to their unique biological activity [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%